Nymph inadvertently described as new species for a fourth time? On the identity of Euscelimena hardi (Tetrigidae: Scelimeninae) with general remarks on the identification of pygmy grasshopper nymphs - Skejo, Josip; Gupta, Sunil Kumar; Tumbrinck, Josef (Zootaxa, 2018)
Euscelimena hardi Gupta et Chandra, 2018 was described earlier this year from Chhattisgarh (India) as a unique species within the genus, characterized in small size, long pronotal projections, and a lack of wings. In this commentary we provide evidence that E. hardi is a nymph of E. harpago (Serville, 1838), hence a new synonymy is proposed: Euscelimena harpago (Serville, 1838) = Euscelimena hardi Gupta et Chandra, 2018 syn. nov. Since this is the fourth time a nymph of Euscelimena Günther, 1938 has been described as a new species, we present general remarks on how to distinguish pygmy grasshopper nymphs and adults. Presence of a groove on the dorsal margin of the hind femora, directly before the knee (separating antegenicular and genicular teeth) is the only definite feature to separate nymphs from adults in brachypronotal or micropronotal wingless species. In macropterous species, morphology of tegmina and alae is helpful to separate nymphs from adults, nymphs having alae rich in radial venation in front of tegmina, while in adults tegmina are in front of developed alae. When dealing with a potential new species, researchers should firstly take into account known pygmy grasshoppers fauna of the studied area via Orthoptera Species File Online database Complex search (with imput Scope of search: Tetrigidae, Place name from geographic hierarchy: continent or country name).